Impact of grain-coating iron minerals on dielectric response of quartz sand and implications for ground-penetrating radar - Josh, M.; Lintern, M.; Kepic, Anton; Verrall, M. (Society of Exploration Geophysics, 2011)
An unexpected result of ground-penetrating radar (GPR) surveys in the Great Victoria Desert (South Australia) was the lack of returning signal in what appeared to be a favorable environment for GPR, with dry silica sand and calcrete aggregates in the near surface. We found that the dielectric response of the dry sand samples had much higher dielectric losses than comparable sands from Western Australia and that the dielectric losses are controlled by the presence of iron oxide minerals, although iron concentrations themselves are only around 0.4%. The samples contained over 90% quartz, with subsidiary amounts of carbonates, kaolin, and smectite occurring with the iron oxide minerals as a coating on the quartz grains. An acid washing procedure removed the reducible iron oxide minerals from the clay coating but left the clays substantially unaltered. Subsequent dielectric and magnetic analysis of the samples indicates that the iron oxide minerals removed during the washing process are responsible for the reduction of GPR penetration at 250 MHz from approximately 10 m to only 1 m.